Comparative Transcriptome Profiling of mRNA and lncRNA Related to Tail Adipose Tissues of Sheep - Ma, Lin; Zhang, Meng; Jin, Yunyun; Erdenee, Sarantsetseg; Hu, Linyong; Chen, Hong; Cai, Yong; Lan, Xianyong (Frontiers in Genetics, 2018)
The Lanzhou Fat-Tail sheep (LFTS, long fat-tailed sheep) is an endangered sheep breed in China with a fat tail compared to the traditional local varieties, Small Tail Han sheep (STHS, thin-tailed sheep) with a small tail, and Tibetan sheep (TS, short thin-tailed sheep) with a little tail. However, little is known regarding how tail fat deposition is regulated by long noncoding RNA (lncRNA). To evaluate the lncRNA and mRNA associated with tail fat deposition and development among these breeds, high-throughput RNA sequencing of three individuals each of LFTS, STHS and TS were performed and analyzed in this study. RNA sequencing data from these three groups revealed 10 differentially expressed genes and 37 differentially expressed lncRNAs between the LFTS and STHS groups, 390 differentially expressed genes and 59 differentially expressed lncRNAs between the LFTS and TS groups, and 80 differentially expressed genes and 16 differentially expressed lncRNAs between the STHS and TS groups (p-value < 0.05 and fold change ≥ 2), respectively. Gene Ontology and pathway analysis of differentially expressed mRNA and target genes of differentially expressed lncRNAs revealed enrichment in fatty acid metabolism and fatty acid elongation related pathways that contribute to fat deposition. Subsequently, the expression of fourteen differentially expressed genes and six differentially expressed lncRNAs were validated by real-time quantitative PCR. Finally, two co-expression networks of differentially expressed mRNA and lncRNAs were constructed. The results suggested that some differentially expressed lncRNAs (TCONS_00372767, TCONS_00171926, TCONS_00054953 and TCONS_00373007) may play crucial roles as core lncRNAs in tail fat deposition processes. In summary, the present study extends the sheep tail fat lncRNA database and these differentially expressed mRNA and lncRNAs may provide novel candidate regulators for future genetic and molecular studies on tail fat deposition of sheep.